NEW COLLECTION OF CONOHYUS SINDIENSIS, A MIDDLE MIOCENE SUID, FROM CHAKWAL, PAKISTAN. - S. Aslam; A. M. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2015)
New fossils of Conohyus sindiensis have been collected from Middle Miocene localities of Lawa, Kallar Kahar and Dhok Bun Ameer Khatoon in district Chakwal. Conohyus sindiensis is very common suid in the Chinji type area of Pakistan. Its biostratigraphic range varies between Kamlial type areas to the base of Nagri Formation. The probable time range of C. sindiensis is from 15 to 11 million years. The sample comprises isolated molars. The morphometric description of these specimens will add new information regarding molar morphology as well as the biogeographic distribution of Conohyus sindiensis. surrounding the Miocene deposits. Geographical
Keywords: Lower Siwaliks; Chinji; Lawa; Dhok Bun Ameer Khatoon; Suidae; Mammalia.